An investigation into control techniques for cascaded plants with buffering, to minimise the influence of process disturbances and to maximise the process yield - Gryffenberg, Jolandi (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.